2000
DOI: 10.1002/hep.510310221
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hyperthermic preconditioning on postischemic hepatic microcirculatory disturbances in an isolated perfusion model of the rat liver

Abstract: Sublethal hyperthermia and the following recovery from this heat exposure, referred to as hyperthermic preconditioning, elicits a transient state of tolerance to oxidative insults through an intracellular protective response: stress response. The impact of hyperthermic preconditioning on hepatic microcirculatory disturbance, which is one of the determinants of ischemia/reperfusion-induced injury of the liver, was investigated by using intravital fluorescence microscopy. Thirty minutes of ischemia and a subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
46
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 37 publications
2
46
0
Order By: Relevance
“…I/R injury is a common consequence of hepatic surgery, particularly following hepatectomies and liver transplantation, and is complicated by microcirculatory failure, followed by necrosis and cell death (23,39). In this context, oxidative damage is thought to play an important role, including the outcome of organ transplantation.…”
mentioning
confidence: 99%
“…I/R injury is a common consequence of hepatic surgery, particularly following hepatectomies and liver transplantation, and is complicated by microcirculatory failure, followed by necrosis and cell death (23,39). In this context, oxidative damage is thought to play an important role, including the outcome of organ transplantation.…”
mentioning
confidence: 99%
“…Preconditioning strategies effective in the laboratory include ischemic preconditioning (IPC), anesthetic preconditioning, hyperthermic or heat-shock preconditioning, and pharmacological preconditioning. [1][2][3][4][5][6][7] In the past decade, serious efforts have commenced to translate some of the robust benefits of preconditioning against ischemia reperfusion (RP) to the clinical arena. Although all of the preconditioning methods offer potential clinical benefits, much of the initial translational effort has focused on IPC, probably due to its extensive and consistently beneficial laboratory experience.…”
mentioning
confidence: 99%
“…In the kidney, the effect of the heat shock response and HSPs to protect against ischemic injury remain controversial (9,14,15). Recently, it has been suggested that prior heat shock reduces the inflammatory reaction (16), which is one of the major mediators of ischemia/reperfusion injury (17,18), and attenuates a postischemic microcirculatory disturbance (19,20). Prior heat shock suppresses cytokine-induced interleukin-8 and tumor necrosis factor-␣ expression and the translocation of the p65 subunit of NF-B (18).…”
mentioning
confidence: 99%